The Concept and Applications of Learning Experience Design - Tuntivivat, Sudarat; Chuenphitthayavut, Krittipat (The Periodical of Behavioral Science, 2024)
Human learning management has reached a new paradigm shift from instructional design to learning experience design, which is an important process for creating learning experiences that enable learners to achieve their goals with humans at the center. The purpose of this article is to present the concept and applications of learning experience design, starting with the identification of the definition of learning, lifelong learning, the difference between learning experience design and instructional design, and the applications of learning experience design such as user experience design and gamification. The implication of learning experience design is the creation of innovative learning from interdisciplinary knowledge to drive change.